Hypertext signs of the guidebook as a basis for its interactivity - Savchenko L. V., Shum O. Y. (Interactive science, 2016)
the article explores the ways to optimize the size of the printed guide. As a result, being an edition with creolized text, the guide has components, which modernization will facilitate the introduction of interactive features into traditional genre model. As specific examples, the author offers to use activity elements in the printed guidebook from the formats that are widely used in children's literature, namely from the panorama book (three-dimensional images, inserts, paper engineering) and travel diary («journaling»).
Keywords: формат; интерактивность; гипертекст; инновационные подходы; innovative approaches; путеводитель; жанровая модель; справочное издание; книга-панорама; дневник путешествий; guide; genre model; hypertext; interactivity; format; a reference book; a book-panorama; travel blog